Anti-TNF-α Therapy Suppresses Proinflammatory Activities of Mucosal Neutrophils in Inflammatory Bowel Disease - Zhang, Cui; Shu, Weigang; Zhou, Guangxi; Lin, Jian; Chu, Feifei; Wu, Huili; Liu, Zhanju (Mediators of Inflammation, 2018)
Neutrophils have been found to play an important role in the pathogenesis of inflammatory bowel disease (IBD), and anti-TNF-α mAb (i.e., infliximab) therapy is demonstrated to be effective in the induction of clinical remission and mucosal healing in these patients. However, how anti-TNF-α mAb regulates the functions of neutrophils is still unknown. Herein, we found that anti-TNF-α therapy significantly downregulated infiltration of neutrophils in inflamed mucosa of IBD patients. Importantly, anti-TNF-α mAb could inhibit neutrophils to produce proinflammatory mediators, such as ROS, calprotectin, IL-8, IL-6, and TNF-α. These data indicate that TNF-α plays a critical role in the induction of mucosal inflammatory response, and that blockade of TNF-α modulates intestinal homeostasis through balancing immune responses of neutrophils.